FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL EXPENDITURE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2013 - Ita Destriyani, 10.05.52.0095; Sulistyowati, Yeye (Students Journal of Accounting and Banking, 2015)
This study was conducted to examine the effect insider ownership, investment opportunity , internal cash flow, and size of the capital expenditure. The populations of this study is manufacturing companies which are listed in Indonesia Stock Exchanged during 2010-2013. The purposive sampling was used in this study. The writer has selected 19 manufacturing companies as sample in this study. The writer used multiple linear regression analyse and using t-test to analyse, the significant level of the test covering normality test, multicollibearity, heteroscedasticity test and autocorrealation test. The result of the study can be concluded that the investment opportunity and size of the company have a positive effects on capital expenditure. While internal cash flow and insider ownership negatively effects capital expenditure. For furtner research , writer is recommended to examine all companies listed on the IndonesianÂ stock exchange, not only manufacturing compaies alone but to all companies.Keywords: Capital Expenditure, Insider Ownership, Invesment Opportunity, Internal Cash Flow, Size